2017
DOI: 10.1111/jofi.12540
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomics of Shadow Banking

Abstract: We build a macrofinance model of shadow banking—the transformation of risky assets into securities that are money‐like in quiet times but become illiquid when uncertainty spikes. Shadow banking economizes on scarce collateral, expanding liquidity provision, boosting asset prices and growth, but also building up fragility. A rise in uncertainty raises shadow banking spreads, forcing financial institutions to switch to collateral‐intensive funding. Shadow banking collapses, liquidity provision shrinks, liquidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(39 citation statements)
references
References 109 publications
0
25
0
Order By: Relevance
“…In boom years, the SBS transforms risky assets into short-term money-like instruments held by households, fi rms and institutional investors. However, liquidity and credit conditions sharply contract in the burst period (Moreira and Savov, 2017). Also, since the SBS off ers an alternative source of funding to the real economy, we may expect that some portion of the additional demand for money will be satisfi ed by shadow banking entities.…”
Section: Resultsmentioning
confidence: 99%
“…In boom years, the SBS transforms risky assets into short-term money-like instruments held by households, fi rms and institutional investors. However, liquidity and credit conditions sharply contract in the burst period (Moreira and Savov, 2017). Also, since the SBS off ers an alternative source of funding to the real economy, we may expect that some portion of the additional demand for money will be satisfi ed by shadow banking entities.…”
Section: Resultsmentioning
confidence: 99%
“…Since the Chinese-style shadow banking is affiliated to the commercial banks, analysis of shadow banking's risk transmission mechanism and the issue of how shadow banking causes systemic risks requires analysing the monetary policy transmission effects on the traditional commercial banks. Moreira and Savov (2017) pointed out that shadow banking securitization products during the boom period are effective tools to supplement market liquidity, but it will exacerbate negative economic volatility when facing uncertain factors. Yang et al (2019) found that the coordination of monetary policy and macro-prudential policies in China through the frontier analysis of effective policies is conducive to stabilizing the economy while reducing the relative scale of shadow banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As we all know, economic fluctuation has an impact on the banking system [50]. To better explore the shock of macroeconomic fluctuation on the banking system with shadow banking (U = 100 and V = 300), we added the traditional banking system for comparison (U = 400 and V = 0).…”
Section: The Shock Of Macroeconomic Fluctuation On the Stability Of Tmentioning
confidence: 99%